Triple Death in Sewer Hole - Büyük, Yalçın; Kurnaz, Gülay; Özbay, Mehmet; Kır, Muhammed Ziya (The Bulletin of Legal Medicine, 2007)
Hydrogen Sulphide (H2S) is a colorless gas that is heavier than air and has a specific rotten egg smell. This gas is a product of fermentation of organic substances and present in the sewer system and refineries of waste fluid. In the sewer system, it forms the “sewer gas” by combining with C02 and methane. The levels above the 500 ppm of H2S is known to cause death but lethal blood level is reported to be 0.9-3.8 % mg/1. Almost all fatalities are accidental origin. Soluble salts of Hydrogen sulphide and sulphides are potent toxins and mode of action is thought to be due to the inhibition of cytochrome oxidase which takes role in intracellular respiration. There is no characteristic autopsy finding of these intoxication cases. Sulfides rapidly disappear in biological samples. Determination of the cause of death in these cases depends on the evaluation of the findings of death scene and autopsy together with the findings of toxicological analysis. In this case report we intended to share the autopsy and toxicological analysis findings of a father and his two sons who were intoxicated when working in the connection line of the sewer system of their house. Key words: Hydrogen sulfide, sewer hole, poisoning, chemical asphyxia, toxicology, autopsy